2009
DOI: 10.1111/j.1365-2249.2009.04042.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic women show reduced T helper type 1 alloresponses to fetal human leucocyte antigen mismatch during pregnancy

Abstract: SummaryLow-level alloreactivity between mother and fetus may provide stimulation for fetal T helper type 1 (Th1) cell immune maturation. This study explored the effects of human leucocyte antigen (HLA) mismatch on materno-fetal interactions detected as cytokine responses and lymphoproliferation in mixed lymphocyte reactions, and whether this was altered in allergic women (n = 62) who have a Th2 propensity compared with non-allergic women (n = 65). HLA-DRb1 mismatch was associated with significantly increased T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…The non-allergic women showed decreased allergen-induced IL-13 secretion in late gestation while the IL-13 secretion remained high in the allergic women [151]. Furthermore, allergic women had reduced IFN-γ and IL-10 production in response to fetal and paternal alloantigens during and after pregnancy [134][135][136].…”
Section: Allergy and Pregnancymentioning
confidence: 97%
See 1 more Smart Citation
“…The non-allergic women showed decreased allergen-induced IL-13 secretion in late gestation while the IL-13 secretion remained high in the allergic women [151]. Furthermore, allergic women had reduced IFN-γ and IL-10 production in response to fetal and paternal alloantigens during and after pregnancy [134][135][136].…”
Section: Allergy and Pregnancymentioning
confidence: 97%
“…Allergic women had reduced IFN-γ and IL-10 production in response to fetal and paternal alloantigens during and after pregnancy [134][135][136]. Furthermore, low IFN-γ and high IL-4 and IL-5 production has been observed in allergic individuals after stimulation with bacterial antigens, i.e.…”
Section: Allergy and Pregnancymentioning
confidence: 99%
“…Further, allergic women have showed significantly lower IFN-γ and relative Th1/Th2 responses to fetal HLA-DRβ1 mismatch during pregnancy (Prescott et al 2009). In a previous study, we found similar responses toward paternal and unrelated pooled antigens in allergic and non-allergic women in the same cohort as in the present study (Persson et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a lower relative Th1/Th2 production was observed in allergic pregnant women by mixed leukocyte reactions (MLR) using irradiated cord blood cells as a proxy for fetal antigens (Breckler et al 2008;Prescott et al 2009). We have previously developed an MLR using inactivated paternal cells as a proxy for allogeneic fetal cells (Ekerfelt et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…К таким факторам относят матерей-атопиков, а также измене-ния в составе кишечной микрофлоры. Как показывают данные современных исследований, среда оказывает эпигенетическое влияние на экспрессию генов иммун-ного ответа у матери, что в свою очередь может влиять на иммунный ответ ребенка [2][3][4], повышая риск реали-зации генетической предрасположенности к заболева-ниям, в т. ч. и аллергическим.…”
unclassified